Relationship between dietary flavan-3-ols intake and mortality in metabolic syndrome population; a large cohort study - Wanjia Zhang; Qian Zhou; Weiqing Yang; Xiaoqin Tan; Yin Xu; Zhan Yi (Frontiers in Nutrition)
BackgroundMetabolic syndrome (MetS) is a global health concern linked to increased mortality. Diets rich in plant-derived compounds, such as polyphenols, have shown potential health benefits for MetS. Among these, flavan-3-ols, a class of commonly occurring polyphenolic compounds, are known for their antioxidant and anti-inflammatory properties. Therefore, we hypothesize that flavan-3-ols intake is negatively associated with mortality risk in MetS population.MethodsThis study analyzed NHANES data (2007–2008, 2009–2010, and 2017–2018). Flavan-3-ol and monomer intake were obtained from the USDA Flavonoid and FNDDS databases. Associations with mortality were assessed using Cox regression, survival differences were compared using Kaplan–Meier curves, and non-linear trends were examined using restricted cubic splines. Subgroup analyses were conducted to explore potential effect modifications.ResultsOver a median follow-up period of 114 months, 1,856 participants survived, while 329 deaths were recorded. In Model 3, participants in the highest tertile (T3) of flavan-3-ol intake exhibited a 33% lower risk of all-cause mortality compared to those in the lowest tertile (T1) (HR = 0.67, 95%CI: 0.49–0.92). For monomers, the hazard ratios ranged from 0.55 for higher levels of epigallocatechin to 0.71 for higher levels of gallocatechin. Kaplan–Meier curves indicated significant differences in survival status across dietary flavan-3-ol intake groups. However, no association was found between flavan-3-ol intake and cardiovascular mortality risk. Additionally, restricted cubic spline (RCS) analysis did not reveal any non-linear relationship, and no significant interaction effects were observed in the subgroup analysis.ConclusionHigher dietary intake of flavan-3-ols is negatively associated with mortality risk in MetS population.